Use of geostatistical as analysis tool to formalize results in the field of electrosmog (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2015)
This paper shows an application of geostatistics as fundamental tool to the analysis of an variable whose behavior has dependence with its space distribution or localization, in a particular place. Particularly this article presents the results for the analysis of the levels of electromagnetic pollution in the city of Lugano (Switzerland) using statistical techniques and interpolation space (geostatistical estimation procedures, known as“kriging”), using freeware toolslike GoogleMaps and statistical analysissoftware R.The samples were acquired from measurements made by the research group TTHF (Telecom, telemetry and high frequency) in the city of Lugano on bands where mobile telephone works (900MHz, 1800MHz and 2100MHz) using the probe electric field (NARDA PMM 8057-FTP).
Keywords: electromagnetic contamination; geostatistics; krigin; mobile telephone